Population characteristics of the lake trout in the Canadian Arctic reference lakes used to calibrate the lake trout population dynamics models described in Campana et al (2020; Suppl Table 2 in Nature Climate Change) - Steven Campana (Knowledge Network for Biocomplexity, 2020)
Supplementary Table 2. Population characteristics of the lake trout in the Canadian Arctic reference lakes used to calibrate the lake trout population dynamics models. All values were observed except estimated values indicated by *